MEMPERCEPAT USIA PROYEK MENGGUNAKAN METODE PERT DAN CPM UNTUK PENGEMBANGAN SISTEM APLIKASI KOMPUTER - Rachmat Adi Purnama (LPPM Universitas Bina Sarana Informatika, 2009)
At the time a development project application systems are often responsible for the projectconstraints of time needed to complete the project itself, where the time is set based on the approximateduration of each activity that must be done according to the plan changes from manejement. Based onthe problems, then a solution is required to determine the activities which can be complete. Thepurpose of writing this journal is to provide a solution in overcoming the problems associated with theacceleration time of a project application development system, while the purpose of writing thisjournal is to apply methods of PERT and CPM in the age of speed or time required in completing aproject according to the age plan (UREN). Research methods that do the authors use the method ofstudy literature, and descriptive method by using the table-table operational variables. At the end ofthe discussion of the results will be described how the age estimates (UPER) can be adjusted to the ageof the plan (UREN) long with a new activity, so that the responsible project can implement the projectin accordance with the target time is planned by managementKeys : PERT, CPM, UPER, UREN